Sistema nacional de avaliação da educação superior (SINAES): contribuições ao bacharelado em administração pública do Instituto Federal Da Paraíba com vistas à melhoria do processo avaliativo - Paiva, Marcos Vasconcelos (2020)
The evaluation of quality in higher education was definitely inserted in the historical panorama of educational public policies, especially with the Sistema Nacional de Avaliação da Educação Superior - SINAES - in 2004. The system aims to ensure the national process of evaluation and regulation of higher education institutions, undergraduate courses and student performance, with the objective of improving the quality of education and guide the expansion of its offer. As a continuous process, evaluation has become an integrated aspect to the management and planning of institutions and undergraduate courses, determining part of their actions to meet the specifications of evaluation procedures and instruments. Within this context is the Bacharelado em Administração Pública (BAP), a undergraduate course in the modality of distance learning offered by the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba (IFPB) in its campus João Pessoa. The challenges inherent to BAP as a distance learning course, belonging to an institution that fits the new tasks integrated to the higher education institutions, highlights the need to identify which management practices of BAP would make possible the improvement of evaluation processes based on the theoretical and methodological references recommended by SINAES. The general objective of the research is to identify potential management actions for the BAP, in view of the instrument for the evaluation of undergraduate courses update in 2017, centering on the instrument used for course renewal. The research consists of a case study, of an applied nature, qualitative approach and descriptive objective, with data collection performed by bibliographic and documentary procedures. For data interpretation, SWOT analysis was used as a tool to identify the strengths, weaknesses, opportunities and threats of the course, through the concepts obtained by the performance indicators present in the last external on-site evaluation report of the BAP. Five indicators with concept 3 were defined, as the lowest value obtained in the evaluation report, organized and analyzed through SWOT matrices: institutional didactic material; full-time teacher ́s work cabinets; work space for course coordination and academic services; teachers' room; and classrooms. Still under analysis, four new indicators were highlighted, included in the new instrument for the evaluation of undergraduate courses, with proven application to the BAP: knowledge, skills and attitudes needed for tutoring activities; virtual learning environment; multidisciplinar team; and experience in teaching at distance learning. From the perspective of analysis criterion and additive criterion present in the indicators highlighted for the research, fifteen proposals for actions were listed to the BAP - eleven to the weak points of the course and four to the new indicators - in the context of providing course managers with complementary knowledge and assist them in making decisions, in order to realize the new demands of the instrument for the evaluation of undergraduate courses, aiming to improve the quality of the evaluation process in the future evaluations for the renewal of the course